2013
DOI: 10.1142/s2010495213500024
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at the Characteristics of Stock Holdings of Foreign and Local Investors in the Indonesian Stock Exchange (Idx)

Abstract: This study provides an overview of the characteristics of stockholdings of foreign and local investors in terms of firm sizes, price levels and liquidity. There are four key findings. First, the IDX is a highly concentrated market and foreign investors dominate the ownership of high market capitalization stocks. Second, foreign investors trade less frequently than domestic counterparts. Third, small, illiquid lower priced stocks dominate this market with domestic individual investors holding most of the stocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Bonser-Neal et al (1999) examined the price impact of trades in the Indonesian equity market using opening, closing and daily VWAPs and found that foreign trades had a significantly larger price impact than local trades. Sudiman et al (2013) examined characteristics of stockholdings of foreign and local investors in terms of firm size, price levels and liquidity. They reported that foreign investors dominated the ownership of large capitalization stocks and traded less frequently than domestic counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bonser-Neal et al (1999) examined the price impact of trades in the Indonesian equity market using opening, closing and daily VWAPs and found that foreign trades had a significantly larger price impact than local trades. Sudiman et al (2013) examined characteristics of stockholdings of foreign and local investors in terms of firm size, price levels and liquidity. They reported that foreign investors dominated the ownership of large capitalization stocks and traded less frequently than domestic counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%